Transitions in School Funding: The Case of Estonia - Rosalind Levacic (Slovo, 2020)
This article traces changes in school financing policy in Estonia since independence in 1991. Estonia, in common with many other transition states, has reformed its school finance system since the collapse of communism, replacing a centralized system run by regional administrative units of central government with per pupil grants for elected local governments. These reforms were driven by political decentralization, which revived numerous small units of local government. As these municipalities were charged with responsibility for general education, a new method of determining education grants to support education expenditures was required. In the course of the 1990s, the earlier method of basing grants mainly on historical expenditure was replaced by determining municipal education grants in relation to the number of pupils. This funding method puts pressure on local governments to organize an efficient school network by adjusting the number of schools, classes, and teachers in line with the number of students. However, as pupil numbers plummeted, opposition grew to school closures which are blamed for exacerbating rural depopulation. In response to these political pressures per pupil funding was modified in 2008 so that the funding method discriminates in favour of high cost small schools in rural communities.